Modeling The Way Strategy to Improve Student Activities and Learning Outcomes in Islamic Education Learning at SD Negeri 3 Babahrot - Darmawan; Dewi, Eka (Jurnal Profesi Guru Indonesia, 2025)
This study aims to evaluate the effectiveness of the Modeling the Way strategy in improving the abilities and activities of third grade students of Elementary School 3 Babahrot in performing Sunnah Rawatib prayers. This study uses a quantitative approach with a pre-test and post-test experimental design, as well as observation and interviews. The sample of this study consisted of two groups, namely the experimental group using the Modeling the Way strategy and the control group taught with conventional learning methods. The results of the study showed that there was a significant increase in students' abilities and activities in performing Sunnah Rawatib prayers in the experimental group after the Modeling the Way strategy was implemented. This can be seen from the significant increase in pre-test and post-test scores in the experimental group, while the control group only experienced minimal improvement. In addition, the results of observations showed that students in the experimental group were more active and involved in learning Sunnah Rawatib prayers compared to the control group. Interviews with students, teachers, and parents also revealed that students in the experimental group were more motivated to perform Sunnah Rawatib prayers regularly, both at school and at home. This study concludes that the Modeling the Way strategy has proven effective in improving students' abilities and activities in performing Sunnah Rawatib prayers. Therefore, the implementation of this strategy is recommended to be implemented in other schools to support students' spiritual development and improve worship practices in daily life.